Equity and Efficiency in Evaluation of Public Programs - Azzi, Corry F.; Cox, James C. (Quarterly Journal of Economics, 1973)
I. Specification of an objective function, 497. — II. Ranking a set of feasible programs, 499. — Conclusion, 501.